PENGARUH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARD TERHADAP CATATAN AUDITOR - Dhany Guno Samekto; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This study aims to determine the effect of the International Financial Report Standards (IFRS), to understand how to influence the adoption and application of IFRS to the auditor's records.This study attempts to understand developments in the field of auditing and accounting.The study was conducted using quantitative methods using secondary data. The   sampling method used was purposive sampling with the specified character. The sample used in this study were 82, but there are as many as 13 outlayer that the sample to 69. The analysis technique used is linear regression analysis. Analysis is performed either simultaneously with the test and the partial F test through test t test. The results of the analysis indicate that the variable changes in the explanatory notes in accordance IFRS equity adjustments and changes in the amount proposed by the notes accompanying the financial statements in accordance with GAAP have significant to change the number of records auditors before and after IFRS justification.